MPZL1 promotes tumor cell proliferation and migration via activation of Src kinase in ovarian cancer - Chen, Danni (Oncol Rep, 2019)
Tumor metastasis is the leading cause of mortality in patients with advanced ovarian cancer. Myelin protein zero like 1 (MPZL1) is a transmembrane glycoprotein that promotes migration of hepatocellular carcinoma cells and is involved in extracellular matrix-induced signal transduction. However, the functional role of MPZL1 in ovarian cancer has not been well elucidated. The present study conducted western blotting, phase-contrast imaging and immunohistochemistry to reveal the functions of MPZL1 in ovarian cancer. The present study demonstrated that the expression levels of MPZL1 were associated with malignant features of ovarian cancer. Furthermore, overexpression of MPZL1 significantly promoted cell proliferation, migration and invasion of ovarian cancer cells. Conversely, MPZL1 depletion by short hairpin RNA inhibited migration and invasion of ovarian cancer cells. In addition, this study demonstrated that phosphorylation of Src kinase was increased upon MPZL1 overexpression. Additionally, phosphorylation and activation of pro-metastatic proteins p130 and cortactin were induced by phosphorylated Src kinase. Collectively, these findings indicated that MPZL1 may be a novel pro-metastatic gene, which promotes tumor cell proliferation and migration through Src-mediated phosphorylation of p130 and cortactin in ovarian cancer.